Brittle Fracture of 2D MoSe2. Issue 2 (3rd November 2016) - Yang, Yingchao; Li, Xing; Wen, Minru; Hacopian, Emily; Chen, Weibing; Gong, Yongji; Zhang, Jing; Li, Bo; Zhou, Wu; Ajayan, Pulickel M.; Chen, Qing; Zhu, Ting; et al.
Abstract : An in situ quantitative tensile testing platform is developed to enable the uniform in‐plane loading of a freestanding membrane of 2D materials inside a scanning electron microscope. The in situ tensile testing reveals the brittle fracture of large‐area MoSe2 crystals and measures their fracture strength for the first time.